Predictions for hc and hb production at the LHC - Sudhansu S. Biswal; Sushree S. Mishra; Monalisa Mohanty; K. Sridhar (Physics Letters B)
The production cross sections of hc and hb, the P11 quarkonia can be predicted in Non-Relativistic Quantum Chromodynamics (NRQCD) using heavy quark symmetry. Our study includes predictions for both the integrated cross-section and the transverse momentum (pT) distribution of hc (hb) production at the Large Hadron Collider (LHC), using the decay process hc(hb)→ηc(ηb)+γ, ηc(ηb)→pp‾. We demonstrate substantial discrepancies in integrated cross-section and the pT distribution of P11 quarkonia production at the LHC using Colour-Singlet Model (CSM), NRQCD and modified NRQCD. Measuring these resonances at the LHC could discriminate between these models, thereby offering further insights into the dynamics of quarkonium production. In addition, we compare the recent LHCb data for the integrated cross-section of hc production at s = 13 TeV in the kinematic range 5.0 < pT < 20.0 GeV and 2.0 < y < 4.0 with the theoretical predictions using NRQCD and modified NRQCD. Modified NRQCD gives an agreement with the recent LHCb experimental data.